A piece of the puzzle: analyses of recent strandings and historical records reveal new genetic and ecological insights on New Zealand sperm whales - Palmer E; Alexander A; Liggins L; Guerra M; Bury SJ; Hendriks H; Stockin KA; Peters KJ (My University)
Cetacean strandings provide important opportunities to extend current knowledge on species or populations, particularly for species that are notoriously difficult to study, such as sperm whales Physeter macrocephalus (parāoa). Between 25 May and 9 June 2018, 13 male sperm whales stranded in Taranaki, New Zealand (NZ), with an additional male stranding 1 mo later in Clifford Bay, Marlborough. We profiled these 14 males for mitochondrial DNA (mtDNA) and carbon and nitrogen stable isotopes to examine their similarity to sperm whales from other geographic areas. Analyses of mtDNA revealed 7 haplotypes, including 1 not previously described (‘New’), and an additional haplotype (‘M’) new to NZ that had been previously reported in sperm whales of the Pacific region. Analysis of rare haplotypes found in NZ males suggested genetic links within NZ and the Southwest Pacific. Differences in stable isotope ratios indicated that, despite the close temporal proximity of these stranding events, individuals originated from at least 2 separate groups, with the whale stranded in Clifford Bay identified as being a regular visitor to Kaikōura, South Island. The analysis of stranding records in NZ dating back to 1873 indicated an increase in recorded single strandings since 1970, and a peak in single strandings in the austral summer months, but no seasonality for mass strandings. Sex predicted latitudinal location for single strandings, with 95.1% of female strandings occurring north of 42° S, fitting the general global distribution of female sperm whales limited to lower latitudes. This study provides the first temporal and spatial assessment of sperm whale strandings in NZ and highlights the need for future research on movements and genetic exchange between NZ sperm whales and sperm whales in the wider Pacific region.
Keywords: 0405 Oceanography; 0602 Ecology; 0608 Zoology